PERANCANGAN BRANDING KAMPOENG BATIK JETIS SIDOARJO SEBAGAI UPAYA MELESTARIKAN PRODUK BUDAYA LOKAL - Nugraha, Ekky Fardhy Satria; Bahruddin, Muh; Aziz, Abdul (Jurnal ArtNouveau, 2013)
The purpose of this Kampoeng Batik Jetis Sidoarjo design branding is to preserve the product of local culture. The research is done with qualitative method research namely with take interview, observation, documentation, and literature to get the data that used as supports maker design concept branding. The data were analyzed with using several phase, that is data reduction, data presentation, and conclusion. From the data analysis were found several keyword that is refer to communication branding strategy which has using to get the goals on target audience. After do the analyze towards data, is founding a concept or keyword of design branding that is âSurvivalâ. Concept description of Survival is a manifestation of struggle to survive the onslaught of all globalization of all. In this case âSurvivalâ or struggle to survive is directed at how to maintain the product of local culture traditional batik tulis Kampoeng Batik Jetis Sidoarjo are packed contemporary. The goals of package design contemporarly is to stay guard the local culture traditional batik tulis product in globalization era are demanded a fast paced, interest, and modern on global public at this time. The result of this branding design is to preserve local culture batik Jetis products.